Pendampingan Aplikasi Akuntansi Berbasis MS. Excel Dalam Optimalisasi Pencatatan Akuntansi Pada BUMDes Pandu Barokah Desa Panduman - Nur Laila Sukma Ayu Sumantri; Konrada Aurelita Putri Stefani Wonga; Reza Agustin; Siti Khoiriyah Maulid Nabila; Ulfi Maratul Azizah; Widya Ayu Pribandari; Arisona Ahmad (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Villages are the smallest governmental entities that play a strategic role in improving community welfare through the management of local potential, one of which is through Village-Owned Enterprises (BUMDes). However, many BUMDes still face challenges in financial management due to limited human resource capacity and the lack of adequate accounting systems. This study aims to enhance the accounting capacity of BUMDes managers through the implementation of a Microsoft Excel-based accounting application that is simple, affordable, and aligned with applicable accounting standards (PSAK). The activity was conducted at BUMDes Pandu Barokah, located in Panduman Village, Jelbuk District, Jember Regency, using a mentoring method consisting of five stages: Forum Group Discussion (FGD), education and socialization, training, mentoring, and evaluation. The results of the activity indicate that BUMDes administrators showed improved understanding and skills in preparing financial reports in a systematic and accountable manner. Although further refinement is needed, the implementation of the Excel-based accounting application has proven to be an effective initial solution for establishing more transparent, professional, and sustainable financial governance in BUMDes.